Liminality and Ritual in Ernest Hemingway’s The Old Man and the Sea - Regmi, Dipendra Raj (AWADHARANA, 2025)
This paper examines Santiago’s journey as a ritual in Ernest Hemingway’s The Old Man and the Sea (1952) from a liminal perspective. Liminality is the intermediate state between two phases, where normal boundaries fade away and transformation or a new identity becomes possible. The unusual experience of the protagonist during the fishing trip reflects a ritual shared by the Cuban people. Santiago, the aging protagonist, embarks on an extraordinary fishing expedition in Cuba. He goes eighty-four days without catching a single fish. The crucifixion symbol transforms Santiago’s journey into a ritual. As a widely recognized hero, his actions provide new insights for scholars. Therefore, this paper explores how Hemingway constructs his novella within a liminal space and how Santiago’s journey functions as a ritual. The study uses the concepts of liminality, as developed by Arnold van Gennep and Victor Turner, to interpret the story. Santiago’s heightened perceptions are shown through his energetic performance. The old man’s blue eyes and the blue hue of the sea draw the reader’s attention. Hemingway depicts fishing as an endurance ritual. The liminal aspects of the ritual are reflected through imagery of Christ, symbols of baseball, and lions on the beach. The analysis discusses the separation, liminality, and integration of the protagonist. Through this approach, the research examines how the sacrificial image transforms the journey into a ritual, offering a new perspective for young scholars.